Summer and winter surveys of deep waters of the Hellenic Trench, Greece, provide insights into the spatial and temporal distribution of odontocetes - KF Thompson; T Webber; L Karantzas; J Gordon; A Frantzis (Endangered Species Research, 2023)
The Mediterranean Sea provides habitat for globally threatened cetaceans. The Hellenic Trench is an Important Marine Mammal Area, providing core habitat for sperm whales Physeter macrocephalus and Cuvier’s beaked whales Ziphius cavirostris. Surveys have characterized distributions of these species in near-shore areas (<2000 m deep). Sparse survey effort in deeper waters during winter has allowed speculation that it is not an important habitat in winter. We used passive acoustic monitoring from towed arrays to document cetaceans during summer and winter, covering 18366 km of trackline off the Peloponnese and Crete. We confirmed the acoustic presence of 5 odontocetes: sperm whales (n = 49 encounters; mean depth (x̄): 3360 m; range (R): 1250 to 4210 m), Cuvier’s beaked whales (n = 4; x̄: 3070 m; R: 1970 to 3770 m), Risso’s dolphins Grampus griseus (n = 5; x̄: 3340 m; R: 2250 to 4440 m), striped dolphins Stenella coeruleoalba (n = 2; x̄: 2980 m; R: 2490 to 3470 m) and rough-toothed dolphins Steno bredanensis (n = 1; 3650 m). We also encountered 224 unidentified delphinids, including a potential blackfish (3020 m). We confirmed that these species are present in the Hellenic Trench throughout the year. Given the impact of multiple threats on sperm and Cuvier’s beaked whales in the Hellenic Trench, we suggest that policymakers follow the precautionary approach in managing human activities in the area. Ongoing seismic surveys, hydrocarbon extraction and uncontrolled shipping could have potentially negative effects on these species at the population level and we advise caution in permitting such activities in future